2001
DOI: 10.1002/jctb.401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high shear stress on microbial viability

Abstract: Escherichia coli and Saccharomyces cerevisiae suspensions were submitted to controlled shear stress. Above a threshold value shear stress induced a decrease in micro-organism viability. The threshold of shear stress ef®ciency depended on the micro-organisms, being between 1292 Pa and 2770 Pa for S cerevisiae, and about 1250 Pa for E coli. Above 1810 Pa, E coli cells were disrupted whereas the S cerevisiae cells remained intact. The higher the cellular concentration, the greater the rate of decrease in viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 14 publications
2
40
2
Order By: Relevance
“…Results (Fig. 2f) show that the maximum shear stresses (model I: ~0.173 kPa and model II: ~0.102 kPa) should not cause any harmful effects on the cell viability Lange et al 2001;Legazpi et al 2009;Scragg et al 1988;Shiragami and Unno 1994) and shear-induced movements (Hyon et al 2012;Koh and Marcos 2015;Marcos et al 2009Marcos et al , 2011Marcos et al , 2012Marcos et al , 2014Marcos and Stocker 2006).…”
Section: Lumped-element Model Of Membrane Deflectionmentioning
confidence: 92%
“…Results (Fig. 2f) show that the maximum shear stresses (model I: ~0.173 kPa and model II: ~0.102 kPa) should not cause any harmful effects on the cell viability Lange et al 2001;Legazpi et al 2009;Scragg et al 1988;Shiragami and Unno 1994) and shear-induced movements (Hyon et al 2012;Koh and Marcos 2015;Marcos et al 2009Marcos et al , 2011Marcos et al , 2012Marcos et al , 2014Marcos and Stocker 2006).…”
Section: Lumped-element Model Of Membrane Deflectionmentioning
confidence: 92%
“…The shear stress was only 1.23 fold higher in 8 L stirred tank reactor of constant k L a experiment, corresponding to a shear stress of 4.23 N/m 2 in 2 L control reactor (Table 2). It was shown that shear stress with the value of 12.5 N/m 2 had no significant decrease on cell lysis or cell viability by the wild type of E. coli [34]. Constant t m was reported to be more applicable under microaerobic conditions compare to constant oxygen uptake rate for the scale-up of 2,3-butanediol fermentation by Enterobacter aerogenes in which homogeneity was important [35].…”
Section: Scaling Up Based On Constant K L Amentioning
confidence: 99%
“…901 turns and 8-20 Pa along the poppet walls at flow rates ranging between 75 and 200 mL/min. For comparison, short duration (r 200 ms) shear stresses of $ 1300 Pa and above are required to alter the viability of Escherichia coli ( $ 1800 Pa for cell disruption); between 1300 and 2800 Pa the threshold for affecting viability of Saccharomyces cerevisiae (Lange et al, 2001). In studies with cultured Baby Hamster Kidney cells, shear stress thresholds appear to be time accumulative as would be relevant in stirred tissue culture.…”
Section: Shear Stresses Developed Within the Ff3mentioning
confidence: 98%